2010
DOI: 10.4314/ajbr.v5i3.54004
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of some hematology and biochemical parameters of clinically healthy alsatian and local dogs

Abstract: The effect of breed on serum biochemistry and hematological parameters of clinically healthy dogs was studied by collecting blood from the cephalic vein of ten (10) Alsatian and ten (10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 2 publications
3
11
2
Order By: Relevance
“…Previous studies have reported an absence of breed differences in PCV, HB concentration, MCV, MCH and MCHC between the Nigerian indigenous dog and the German shepherd dog (Olayemi and Ighagbon 2011;Ariyibi et al 2002). Our findings in the present study are consistent with their reports.…”
Section: Breed Differences In Erythrocyte Valuessupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies have reported an absence of breed differences in PCV, HB concentration, MCV, MCH and MCHC between the Nigerian indigenous dog and the German shepherd dog (Olayemi and Ighagbon 2011;Ariyibi et al 2002). Our findings in the present study are consistent with their reports.…”
Section: Breed Differences In Erythrocyte Valuessupporting
confidence: 83%
“…Absence of sex difference in erythrocyte values has been reported in Rotweiller breed of dog (Adebiyi et al 2014), the German shepherd dog (Ariyibi et al 2002;Olayemi and Ighagbon 2011), the Nigerian local breed of dog (Oduye 1978;Olayemi et al 2009), the Nigerian cat (Nottidge et al 1999), and N'dama cattle (Olayemi 2007). The present study reveals no sexual dimorphism in the erythrocyte values of the German shepherd (Table 2).…”
Section: Sexual Dimorphism In Erythrocyte Valuescontrasting
confidence: 48%
See 1 more Smart Citation
“…Mostly, the measured values are within the normal ranges reported so far [9][10][11] . The durations for various chronological parameters following anesthesia induced by thiopental in female subjects in both control and experimental groups are illustrated in Table 2.…”
Section: Resultsmentioning
confidence: 56%
“…At present, there are increasing numbers of this breed of dogs in Nigeria probably due to their resistance to certain haemoparasitic diseases such as canine babesiosis and trypanosomosis that constantly affect exotic breeds (Olayemi et al, 2009). Some works had reported the haematology of the Nigeria local dog (Saror et al, 1979;Ariyibi et al, 2002;Olayemi et al, 2009). However, there is a paucity of information on the serum biochemistry and urinalysis of the Nigerian local dog.…”
Section: Introductionmentioning
confidence: 99%